Lenalidomide in combination with dexamethasone for the treatment of relapsed or refractory multiple myeloma - Palumbo, A.; Dimopoulos, M.; Miguel, J.S.; Harousseau, J.-L.; Attal, M.; Hussein, M.; Knop, S.; Ludwig, H.; Von Lilienfeld-Toal, M.; Sonneveld, P. (Blood Reviews, 2009)
Recent studies have shown a clinical benefit of lenalidomide, an oral immunomodulatory drug, plus dexamethasone in patients with relapsed/refractory multiple myeloma (MM). The most common grade 3-4 adverse events were cytopenias, fatigue, muscle cramps, rash, infection, insomnia, and venous thromboembolism. Lenalidomide in combination with dexamethasone has been approved by the United States Food and Drug Administration and the European Medicines Agency for the treatment of patients with MM who have received at least one prior therapy. An expert panel reviewed the efficacy and toxicity of lenalidomide plus dexamethasone, and provided recommendations on the management of patients receiving this treatment. Patient selection is straightforward, as prognostic factors do not appear to heavily influence efficacy. In addition, the panel agreed on strategies for the management of side effects. The recommendations presented here will aid the safe administration of lenalidomide, and avoid unnecessary dose reduction and discontinuation, thus assuring the best efficacy of treatment. © 2008 Elsevier Ltd. All rights reserved.
Keywords: Cytopenia; Dexamethasone; Lenalidomide; multiple myeloma; Venous Thromboembolism